Design Weekend; Open House 1980 - various authors (Oz, 1980)
A health spa on Isola Bella, Lake Maggiore, Italy. Design Weekend was conceived as an opportunity for professional designers and students to work together in an intense, three day charette situation… [Introduction by Professor David Howard Bell.]